design and analysis of cable stayed bridge with 800 m span - Manan, Mohammad Salman; Bayzoni, Bayzoni; Sebayang, Surya (Universitas Lampung, 2018)
Bridges are constructions that connect people and land transportation that is blocked by obstacles. One of which is the type of cable stayed bridge.. This bridge structure consists of a combination of various structural components such as pylon, cable and deck. The deck is hung with a prestressed cable that is anchored to the pole. Gravitational and lateral forces acting on the bridge deck will be transferred to the ground via cables and pylon. The cable will receive tensile force and the pylon accepts the compressive force. This bridge planned 800 m long, 14 m wide traffic, 1.5 m sidewalk width, elongated girder type is tub girder, 300 mm plate thickness, cable arrangement is 2 fields and fan, and the cable used is VSL 7-wire strand. Girder quality of 290 MPa, concrete quality of 35 MPa, and welding quality of 490 MPa. Bridge model calculations are supported by SAP 2000 and Microsoft Excel programs. From the calculation results obtained the reinforcement design for the sidewalk using the main reinforcement D16-150 mm and reinforcement for D13-200 mm, reinforcement for vehicle floors both in the field and pedestal with the main reinforcement D22-100 mm and reinforcement for D16-100 mm. The dimensions of the girder used were flanges of 1 m x 0.05 m, web 1.3 m x 0.01 m and lower fluxes 4.2 m x 0.04 m. To get a more stable structure design, 3-dimensional analysis is needed. Keywords: Cable Stayed Bridge, Tub Girder, Girder